PERAN GURU PAI DALAM MENCIPTAKAN BUDAYA BELAJAR EFEKTIF - Hana Mukhofiyatun Nisa’; Nur Kholis (Universitas Islam Raden Rahmat Malang, 2019)
This study aims to determine the role of PAI teachers in creating an active learning culture, planting religious values, and how to foster students' enthusiasm for learning. This research was conducted qualitatively with a case study method. Place of research at the State Vocational High School 2 in Kediri City, East Java, Indonesia. The object of this research is the role of PAI teachers, the planting of religious values, and ways to foster the spirit of learning. Principals and teachers are subjects of research. Methods of collecting data through in-depth interviews and observations. The validity of the data is examined through credibility, transferability, dependability, and confirmability techniques. Data analysis was performed, starting from displaying data, reducing data, presenting data, drawing conclusions/verification. The research findings indicate that the role of the teacher as a teacher and educator must be balanced. The teacher teaches students not only to be smart on paper, understands the theory but can practice religious values in daily life such as reading the Koran, reading prayers before learning, memorizing juz 'amma, praying in congregation, discipline, and honest. To foster students' enthusiasm for learning, teachers use a variety of methods. The method used is the dialogue method, practicum method, reward, and punishment method, and the ibrah and want a method. Finally, the goal of learning can be achieved, and learning becomes a culture in the school so that learning can be active.